Factors affecting conception rates in artificially inseminated bovines - THIRUNAVUKKARASU, M; KATHIRAVAN, G (The Indian Journal of Animal Sciences, 2011)
This study was conducted to analyze the factors influencing conception failures in artificially inseminated bovines. Bovines (9000 cattle and 1943 buffaloes) inseminated at different centres were selected at random and considered for the study. The overall conception rate was 34.53% in cows and 25.52% in buffaloes. There was a significant association of the conception rate with different farm sizes and with different land holdings in both cows and buffaloes. Milch animals/heifers less than 3 years of age could achieve a higher conception rate than older animals. There was a significant association of conception rate and age of the animal in both the species. However, the relationship of conception rate with order of lactation, stage of lactation and milk yield was significant in cows alone and not in buffaloes. There was a significant difference between the conception rates observed in both cows and buffaloes with and without reproductive disorders. The conception rate in cows was associated with season, while such association was not seen in buffaloes. As the distance to the AI centre increased, the conception rate achieved had remarkably reduced in both the species of bovines. Doorstep inseminations had rewarded in terms of higher conception rates in both cows and buffaloes.